2021
DOI: 10.1007/s11606-020-06465-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Medicaid Utilization and Spending Associated with Homeless Adults’ Entry into Permanent Supportive Housing

Abstract: BACKGROUND: There is growing interest in financing housing and supportive services for homeless individuals through Medicaid. Permanent Supportive Housing (PSH), which integrates non-time-limited housing with supportive services for people who are disabled and chronically homeless, has seen rapid growth in the last decade, but clear evidence on the long-term impacts of PSH, needed to guide state efforts to finance some PSH services through Medicaid, is lacking. OBJECTIVE: Assess changes in Medicaid expenditure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…One hypothesized reason for this pattern is that some patients may require fewer ED services or hospitalizations over time when receiving more preventive services and better chronic care management in primary care. 31 For example, IPC patients taking prescribed or illicit opioids are educated about and offered naloxone overdose kits, which have shown effectiveness in mitigating overdose risk. 32 Likewise, contextual risks (e.g., environment) for patients engaging in high-risk behaviors or demonstrating symptoms of early progressive chronic diseases can be addressed within an integrated care team to avert adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesized reason for this pattern is that some patients may require fewer ED services or hospitalizations over time when receiving more preventive services and better chronic care management in primary care. 31 For example, IPC patients taking prescribed or illicit opioids are educated about and offered naloxone overdose kits, which have shown effectiveness in mitigating overdose risk. 32 Likewise, contextual risks (e.g., environment) for patients engaging in high-risk behaviors or demonstrating symptoms of early progressive chronic diseases can be addressed within an integrated care team to avert adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Other housing interventions, such as permanent supportive housing, have not shown a similar association with ED visits for PEH with prior high use of acute health services, 29 although there is some evidence these programs may reduce acute care use for the general PEH population. 25 , 26 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…More-recent studies have examined health care utilization and associated costs longitudinally among Medicaid beneficiaries receiving PSH and an observational comparison group in two large systems of care, New Jersey (DeLia et al, 2021) and Pennsylvania (Hollander et al, 2021). Both studies found statistically significant reductions in emergent and inpatient hospital stays while observing an increase in pharmacy spending among PSH recipients.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…Behavioral health tends to be an important contributor of service utilization and costs among individuals experiencing homelessness. For example, behavioral health care costs were the largest driver of spending in the panel study of Medicaid PSH recipients in Pennsylvania (Hollander et al, 2021). As a note of comparison, for the Los Angeles County Housing for Health program, after which this Inland Empire program was modeled in terms of the program eligibility and the supportive housing service delivery model, the posthousing behavioral health service costs were reduced by 26 percent in the treatment group (no comparison group was used) (Hunter et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation